Argument ontology for describing scientific articles: A statistical study based on articles from two research areas. Issue 1 (18th October 2019) - Zhou, Huimin; Song, Ningyuan; Cheng, Hanghang; Wang, Xiaoguang
ABSTRACT: The research provides (1) an account of the construction of a new Scientific Argument Ontology (SAO), (2) a statistical analysis of 40 articles from both fields of Library and Information Science and Biomedical Research, and (3) a summary of important differences between the article structures common to each respective field of study and characteristics of their contents as revealed by applying SAO to conduct qualitative analysis. Ontology coverage ratios as well as the ratios of different classes and evidence types were calculated in the analysis. The results show a comprehensive coverage of SAO, while also indicate that the ontological construction of scientific arguments should fully consider the characteristics of their disciplines and fields in order to better facilitate extraction, discovery and retrieval.